Pengaruh Karakteristik Pemerintah Daerah dan Sistem Pengendalian Intern Terhadap Kinerja Keuangan Pemerintah Daerah (Studi Empiris Pada Provinsi Sumatera Bagian Selatan) - Arta Pradana; Sunardi Sunardi; Muhammad Fahmi (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of the characteristics of the local government and internal control system on the financial performance of the local government in the districts/cities of the province of South Sumatra, Lampung, Bengkulu, Jambi, and the Bangka Belitung Islands. The population in this study was 60 regions/cities in the provinces of South Sumatra, Lampung, Bengkulu, Jambi, and Bangka Belitung Islands, with the sampling method determined was the saturated sample. The data used is secondary data in the form of LKPD for the year 2017-2019. The data collection method in this research is the documentation method. The data analysis method used is descriptive statistical analysis method, classical assumption test, and multiple linear regression, as well as data processing in this research using SPSS 16.0 (Statistical Product and Service Solution) statistical computer program. The results of this study can be concluded that jointly (f test) the variables of local government size, prosperity, intergovernmental revenue, and internal control systems have a simultaneous effect on the financial performance of local governments in the districts/cities of the provinces of South Sumatra, Lampung, Bengkulu, Jambi, and the archipelago. Bangka Belitung. Partially (t-test) shows that the size of local governments, intergovernmental revenue, and internal control systems have no effect on the financial performance of local governments, while prosperity has a significant effect on the financial performance of local governments in the districts/cities of the provinces of South Sumatra, Lampung, Bengkulu, Jambi, and the islands. Bangka Belitung).